Cupping therapy combined with moxibustion in the treatment of chronic gastritis: A case report (拔罐联合艾灸治疗慢性胃炎1例) - WANG Ting (王婷); HUANG Yanping (黄砚萍); TIAN Xiaodong (田小冬) (中西医结合护理)
This paper summarized the treatment effect of cupping therapy combined with moxibustion in a patient with chronic gastritis. The patient with chronic gastritis in the acute phase was treated with drug therapy initially, and non-drug treatment such as cupping therapy and moxibustion were carried out to relieve the pain. After intervention, the Numerical Rating Scale of pain is decreased from 5 to 2. (本文总结拔罐联合艾灸治疗慢性胃炎1例的效果及护理经验。患者处于慢性胃炎急性发作期, 药物治疗未能完全缓解后, 采用非药物疗法, 闪罐、走罐、留罐联合温灸治疗缓解患者疼痛, 疼痛数字评分从5分降到2分, 效果明显。)